Integrated Analysis of mRNA and miRNA Changes in Two Haliotis diversicolor Genotypes and Their Hybrid - Liang, Shuang; You, Weiwei; Luo, Xuan; Ke, Jinwei; Huang, Miaoqin; Guo, Yongjun; Ke, Caihuan (Frontiers in Marine Science, 2021)
Heterosis is a widely distributed phenomenon in mollusks. It is vital in aquaculture by bringing beneficial traits into hybrids. People have utilized the heterosis theory in aquaculture for years. However, the molecular basis of heterosis remains elusive. Evident growth and survival heterosis were shown in the hybrid (“Dongyou-1”) of two Haliotis diversicolor geographic genotypes (Japan and Taiwan). To explore the molecular basis underlying the hybrid abalone’s heterosis, we conducted comparative mRNA and miRNA transcriptional analysis in the hybrid and parental genotypes. Differentially expression analysis identified 5,562 differentially expressed genes (DEGs) and 102 differentially expressed miRNAs (DEMs) between the three genotypes. 1,789 DEGs and 71 DEMs were found to be non-additively expressed in the hybrid. Meanwhile, both the expression level dominance pattern (ELD) and expression level overdominance pattern (ELOD) were found in the DEGs and DEMs, showing the existence of dominance and overdominance models in the hybrid’s transcriptome and post-transcriptional regulation. Functional analysis showed the non-additively expressed genes, ELD genes, and ELOD genes were significantly enriched in growth, immunity, and stress response related pathways, while some of the pathways were regulated by the mRNA-miRNA interactions. The expression levels of FGF, C1Q, HC, CAT, SEGPX, and MGST were significantly up-regulated in the hybrid compared to the middle parent value. In conclusion, we identified the existence of non-additivity, dominance, and overdominance models in the transcriptome and miRNAome of the H. diversicolor hybrid; these models facilitate the advantageous parental alleles’ integration into the hybrid, contributing to the hybrid’s growth and survival heterosis.